Age‐adjusted D‐dimer cutoff for the diagnosis of pulmonary embolism: A cost‐effectiveness analysis. (28th February 2020) - Blondon, Marc; Le Gal, Gregoire; Meyer, Guy; Righini, Marc; Robert‐Ebadi, Helia
Abstract: Background: In patients with suspected pulmonary embolism (PE) and a non‐high pretest probability, the use of an age‐adjusted D‐dimer cutoff (AADD, <500 ng/mL up to 50 years, then <age × 10 ng/mL) was shown to further reduce the need for computed tomography pulmonary angiography while safely ruling out PE. Our objective was to evaluate its cost‐effectiveness. Methods: We created a decision tree to compare the use of the AADD with the standard D‐dimer cutoff. The model included short‐term venous thromboembolism‐related events and long‐term complications, their associated morbidity/mortality, and costs. Probabilities were derived from published literature and the ADJUST‐PE study, and costs from US estimates. The time horizon was lifetime, with a health care system perspective. Results: Using the AADD cutoff, compared with the standard cutoff, was associated with a loss of 0.0001 quality‐adjusted life‐years (QALY) and an average cost reduction of $33.4. The decremental cost‐effectiveness ratio (DCER) was +$282 881/lost QALY (95% confidence interval from +$43 209/lost QALY to a dominant strategy). The probability that the use of the AADD cutoff was either dominant or gained >$200 000/lost QALY was 79.4%. In sensitivity analyses, the DCER became <+$200 000/lost QALY only if, among patients with D‐dimer below the AADD cutoff,  the mortality of an undiagnosed PE was >6% or the prevalence of PE was >0.6%. Conclusions: The AADD cutoff results in a clinically nonsignificant decrease in QALY but important costs reductions. It is a decrementally cost‐effective innovation, with a potential of cost savings of >$80 million per year for the United States health care system.